Analysis of Water Catchment Area Potential Based on Geographic Information Systems (GIS) Case Study of XIII Koto Kampar District - Chintia Ningrum, Lovia; Adeswastoto, Hanantatur; Azriadi, Emon (Journal of Engineering Science and Technology Management, 2026)
Recharge areas play a crucial role in maintaining hydrological balance and sustaining groundwater resources. Uncontrolled land use change can reduce infiltration capacity and increase environmental risks such as flooding and groundwater depletion. This study aims to analyze and map the potential of groundwater recharge areas using a Geographic Information System (GIS) to support spatial planning and water resource management. The research employed secondary data consisting of rainfall, slope, soil type, and land use. Each parameter was standardized, weighted, and scored according to its influence on infiltration capacity, then integrated using a weighted overlay method within GIS software to produce a comprehensive recharge potential map. The results classify the study area into low, moderate, and high groundwater recharge potential zones. Areas with high recharge potential are predominantly associated with gentle slopes, coarse-textured soils, relatively high rainfall, and land use dominated by vegetation cover, whereas low potential zones are characterized by steeper slopes, fine-textured soils, and built-up land use. The resulting map provides a spatial representation of recharge capacity that can be used to identify priority areas for conservation and guide land use control. This study demonstrates that GIS-based multi-criteria analysis is effective for evaluating groundwater recharge potential and generating practical spatial information. The findings are expected to support decision making in spatial planning, groundwater conservation strategies, and sustainable environmental management, as well as to serve as a reference for future studies related to hydrological assessment and land use planning. It also enhances data integration, transparency, and consistency across planning processes locally.